Across the sand - Howey, Hugh (Howey, Hugh. Sand series., 2022)
"Long after civilization is destroyed, a group of siblings follow in the shadow of their father, combing the barren sands for treasure, searching for a better life, in the long-awaited second novel in the series following Sand"--